2022
DOI: 10.3390/insects13050469
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Distribution of Human-Biting Ticks in Northwestern Spain

Abstract: Ticks transmit a wide diversity of pathogens to a great variety of hosts, including humans. We conducted a tick surveillance study in northwestern Spain between 2014 and 2019. Ticks were removed from people and identified. Tick numbers, species, development stages, the timeline, seasonal and geographical distribution and epidemiological characteristics of people bitten by ticks were studied. We collected ticks from 8143 people. Nymphs of I. ricinus were the most frequently collected. Rhipicephalus bursa, R. sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
10
0
3
Order By: Relevance
“…Our results are of great relevance, considering that the region of Castilla y León has increased reports of tick bites in humans in recent years (Vieira Lista et al 2022). This region has geographical and climatological characteristics that favor the proliferation of multiple tick species and the presence of F. tularensis, Rickettsia spp., Borrelia spp., and Crimean-Congo hemorrhagic fever virus (Portillo et al 2018, Monsalve Arteaga et al 2020, Mínguez-González et al 2021).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our results are of great relevance, considering that the region of Castilla y León has increased reports of tick bites in humans in recent years (Vieira Lista et al 2022). This region has geographical and climatological characteristics that favor the proliferation of multiple tick species and the presence of F. tularensis, Rickettsia spp., Borrelia spp., and Crimean-Congo hemorrhagic fever virus (Portillo et al 2018, Monsalve Arteaga et al 2020, Mínguez-González et al 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Likewise, a recent study showed fluctuating distribution patterns of ticks with their potential to transmit several pathogens throughout northwestern Spain. These findings demonstrate the importance of monitoring the dispersion of these arthropods and the pathogens transmitted (Vieira Lista et al 2022). To emphasize, in Spain, there are numerous reports of diseases, including Q fever and tularemia, which are caused by Coxiella burnetii and Francisella tularensis , respectively.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A recent survey of ticks in Spain reveals an increasing number of tick vector with CCHF. Dermacentor-borne necrosis erythema and lymphadenopathy are becoming an emerging disease in Spain [ 105 ]. Furthermore, tick bites have become frequent in spring and winter in Spain, in line with warmer winter due to GW over the years [ 103 , 105 ].…”
Section: Important Vbds Posing Threats To the Mediterranean Regionmentioning
confidence: 99%
“…Dermacentor-borne necrosis erythema and lymphadenopathy are becoming an emerging disease in Spain [ 105 ]. Furthermore, tick bites have become frequent in spring and winter in Spain, in line with warmer winter due to GW over the years [ 103 , 105 ]. In Portugal, Mediterranean spotted fever (MSF) is the most important TBD with several fatal outcomes since year 2000 [ 106 ].…”
Section: Important Vbds Posing Threats To the Mediterranean Regionmentioning
confidence: 99%